CRITICAL THINKING AND INTERDISCIPLINARY DEVELOPMENT FOSTERING CRITICAL THINKING IN AN INTERDISCIPLINARY WELLNESS COACHING ACADEMIC PROGRAM - Rowan, Noell; Kommor, Paula; Herd, Ann; Salmon, Paul; Benson, Patricia (European Scientific Journal, ESJ, 2015)
Critical thinking skills are seen as increasingly important in meeting the complex demands of the global workplace (Pithers, 2000). Developing curriculum that crosses and integrates specific disciplines is one important mechanism that institutions of higher learning can use to foster higher-order critical thinking skills among their students (Behar-Horenstein & Niu, 2011; Nosich, 2009). This paper explores the interdisciplinary curriculum development process to develop a minor in Wellness Coaching, where critical thinking was a unifying core component. The steps used in the curriculum development process are described, and implications for interdisciplinary programs focusing on critical thinking skills are examined.